2010
DOI: 10.1002/jcu.20734
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hydrogastric sonography and spiral computed tomography in staging of gastric carcinoma—A comparative study

Abstract: When compared with HPE, HGS was found to be more accurate than helical CT for assessment of T and N staging. Sonographic and helical CT were equally accurate for the assessment of M stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This study combined the findings of Zheng [ 11 ] and Chen et al [ 12 ]. Enhanced MDCT scanning and oral echo agent ultrasound imaging were combined for the T staging of gastric cancer, and the accuracy reached 85.00%, which was consistent with that from Venkataraman [ 28 ]. The combination of enhanced CT scanning and ultrasound imaging has a higher accuracy in the evaluation of preoperative T staging of gastric cancer than any method used alone ( P < 0.05).…”
Section: Discussionsupporting
confidence: 77%
“…This study combined the findings of Zheng [ 11 ] and Chen et al [ 12 ]. Enhanced MDCT scanning and oral echo agent ultrasound imaging were combined for the T staging of gastric cancer, and the accuracy reached 85.00%, which was consistent with that from Venkataraman [ 28 ]. The combination of enhanced CT scanning and ultrasound imaging has a higher accuracy in the evaluation of preoperative T staging of gastric cancer than any method used alone ( P < 0.05).…”
Section: Discussionsupporting
confidence: 77%
“…7 Ultrasonography (USG) and Multidetector Computed Tomography (CT) with Multiplanar Reformation (MPR) gives both physiological as well as anatomical description of the site and extension of lesion within the lumen, as well as beyond the lumen. 4,5 The other modalities which are used are Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET). These examinations are effective to varying degrees and are limited in assessing the site and extension of disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that dedicated transabdominal ultrasound performed after ingestion of boiled cooled water and of a hypotonic agent along with the use of broad band transducers provides detailed and unique evaluation of the stomach. 4 Multidetector CT involves thin-section collimation of the stomach allowing high-quality MPR (Multiplanar Reformations) images which dramatically improves the visualization of fine anatomic details of the gastric wall, adjacent structural involvement, lymph node status and metastatic lesions. 9 In present study, CT showed 87% efficacy, whereas USG showed 80% efficacy with P value < 0.01 which is significant, which shows CT is better modality for diagnosing gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TUS has been recognized as a diagnostic modality for patients with gastrointestinal disorders [6][7][8] and has been used to assess gastric wall thickness and for the preoperative staging of gastric cancer. [9][10][11][12] Ishigami et al 13 reported the usefulness of TUS in early gastric cancer but not in advanced gastric cancer and did not demonstrated the details of TUS imaging. Although the use of TUS to preoperatively diagnose the depth of tumor invasion may benefit patients, few reports have investigated its ability of determining the depth in detail in patients with gastric cancer.…”
mentioning
confidence: 99%